Variability of Ocean Ecosystems around South America (VOCES) - Purca, Sara (2017)
The Large Marine Ecosystems (LME) around South America are highly productive, and diverse, and play an important role in the economy and society of the surrounding countries. These environments are under the effect of climate change, but little is known about how variability at different scales influences their biodiversity and the abundance of the exploited populations. Our work suggests that biodiversity can enhance the resilience of ecosystem structure to environmental trends around South America three Large Marine Ecosystems (LMEs).